2006
DOI: 10.1017/cbo9780511791086
|View full text |Cite
|
Sign up to set email alerts
|

Rightful Resistance in Rural China

Abstract: How can the poor and weak 'work' a political system to their advantage? Drawing mainly on interviews and surveys in rural China, Kevin O'Brien and Lianjiang Li show that popular action often hinges on locating and exploiting divisions within the state. Otherwise powerless people use the rhetoric and commitments of the central government to try to fight misconduct by local officials, open up clogged channels of participation, and push back the frontiers of the permissible. This 'rightful resistance' has far-rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
257
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 915 publications
(260 citation statements)
references
References 0 publications
1
257
0
2
Order By: Relevance
“…Recent research found a new direction of public counteraction toward environmental crisis (Jing, 2000;O'Brien & Li, 2006;Tilt, 2010). By mobilizing citizens' support and employing lenient rhetoric to exert influence on government, this kind of "peaceful" resistance exists and operates at the periphery of the formal political oversight.…”
Section: China's Environmental Civil Societymentioning
confidence: 99%
“…Recent research found a new direction of public counteraction toward environmental crisis (Jing, 2000;O'Brien & Li, 2006;Tilt, 2010). By mobilizing citizens' support and employing lenient rhetoric to exert influence on government, this kind of "peaceful" resistance exists and operates at the periphery of the formal political oversight.…”
Section: China's Environmental Civil Societymentioning
confidence: 99%
“…The mother firm may be an industrial firm or non-industrial, service firm [5]. A wholly owned subsidiary is when a company sets up a new venture in which it owns 100% of its stocks [25]. A unit to be es0 tablished by an industrial firm may be: a sales promotion unit, warehouse unit, R & D unit, technology transfer unit, manufacturing unit, financing unit, holding unit, or an assembly unit.…”
Section: Wholly Owned Subsidiary (Sole Venture)mentioning
confidence: 99%
“…The consequences may outweigh the advantages of WOS. Choosing a wholly owned subsidiary, especially green field is an expensive and difficult entry strategy to China because usually no firm alone can manage all of the high risks associated with this modality [25].…”
Section: Disadvantages Of the Wholly Ownedmentioning
confidence: 99%
See 1 more Smart Citation
“…Social and economic rights that legitimate claims against the control of market forces are either ignored or attacked. In China, while the official citizenship education is tied to discourses of socialism, there were also studies of important empirical studies of localized rights issues in China, which centered on the 'rights-defending movement' (Diamant et al, 2005;O'Brien & Li, 2006). Taiwan's human rights education is one of the most effective in the Asia-Pacific region.…”
Section: Literature About Human Rights and Rule Of Law Educationmentioning
confidence: 99%